Technological characteristics of the wood of two Quercus species from Durango, México - Pérez Olvera, Carmen de la Paz; Dávalos-Sotelo, Raymundo; Limón Godina, Roberto; Quintanar Isaías, Paz Alejandra (Instituto de Ecología, A.C., 2016)
The anatomical characteristics, physical properties, mechanical properties and air-drying speed were determined for the wood of five trees of Quercus sideroxyla Humb. & Bonpl. (red oak) and two of Quercus rugosa Nee (white Oak), collected in three municipalities of the State of Durango. For the macroscopic anatomical study specimens of 12 cm x 7 cm x 1 cm were used and for the microscopic anatomical study, thin slices were cut and used along with fragmented material. Histochemical tests were carried out to determine tannins. The measurable elements were classified based on the average. They included the taxonomic position, morphological characteristics, geographic and altitudinal distribution and common names. The technological characteristics were determined in green and dry conditions, using specimens of various dimensions. The wood of the seven individuals, presented similar characteristics in some cases and different in others between subgenera and differences between individuals of the same subgenus were recorded. The physical characteristics of both species are classified as high to very high; the mechanical properties in both green and dry conditions are classified as hard, stiff and strong in the majority of the cases, with the notable exception of the strength in compression parallel of the two species and shear parallel of Q. rugosa which is moderately strong. The results were compared with data available in the literature for both species, coinciding in many characteristics with the studied in the present work. Based on the results suggested applications are given.